Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio dan Operating Expenses To Operating Income Terhadap Profitabilitas Bank Aceh Periode 2017-2020 - Hafidhah, Hafidhah; Putri Utami, Dayana (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to examine the effect of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), and Operating Expenses to Operating Income (OEOI) on the profitability of Bank Aceh. This study uses a quantitative research approach with Multiple Linear Regression analysis method. This research data uses Bank Aceh monthly financial report data for the 2017-2020 period. Research data obtained by testing the hypothesis performed by statistical tests, namely partial test (t-test) and simultaneous test (f-test). The results of this study indicate that: (1) Third Party Funds, Capital Adequacy Ratio and Operating Expenses to Operating Income jointly affect the profitability of Bank Aceh. (2) Third Party Funds affect the profitability of Bank Aceh. (3) Capital Adequacy Ratio affects the profitability of Bank Aceh. (4) Operating Expenses to Operating Income affect the profitability of Bank Aceh.